2023
DOI: 10.1021/acsanm.3c01935
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Physicochemical Properties of Carbon Nitride Nanoparticles via Precursor Thermal Treatment: Effect on Methyl Orange Photocatalytic Discoloration

Abstract: In this work, we synthesized and characterized carbon nitride (CN) nanoparticles obtained by the thermal treatment (550 °C) of urea, melamine, dicyandiamine, and dicyandiamine-barbituric acid in an open reactor and evaluated the effect of different precursors on the photocatalytic performance. CNs obtained from melamine, dicyandiamine, and dicyandiamine-barbituric acid were 3D melon-type structures. On the other hand, CN obtained from urea was a 2D microporous, amorphous structure whose melon or graphitic arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Consequently, the photocatalytic behavior of g-C 3 N 4 significantly influences and augments the overall photoelectrochemical response in the BT-CN composite, further enhancing its performance. Furthermore, it has been reported that in both darkness and light, , g-C 3 N 4 can promote the oxygen reduction reaction (ORR), and the arguments to be presented later on ORR remain consistent for the BT-CN.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Consequently, the photocatalytic behavior of g-C 3 N 4 significantly influences and augments the overall photoelectrochemical response in the BT-CN composite, further enhancing its performance. Furthermore, it has been reported that in both darkness and light, , g-C 3 N 4 can promote the oxygen reduction reaction (ORR), and the arguments to be presented later on ORR remain consistent for the BT-CN.…”
Section: Resultsmentioning
confidence: 81%
“…Gomis-Berenguer et al , observed a varying trend in the photoelectrochemical response of WO 3 /nanoporous carbon-based photoanodes for photocatalytic water oxidation with different weight ratios of nanoporous carbon, and 20 wt % was found to be the most favorable content of nanoporous carbon. It is noteworthy to mention that the enhanced PEC performance of BT-CN, beyond the intrinsic properties of carbonaceous material, is anticipated not solely due to its typical characteristics but also because of the synergistic photoelectrochemical response arising from the inherent photocatalytic processes exhibited by g-C 3 N 4 . ,, Also, the photoactive nature of g-C 3 N 4 contributes to the observed improvements, creating a distinctive charge accumulation region within the BT-CN composite . Consequently, the photocatalytic behavior of g-C 3 N 4 significantly influences and augments the overall photoelectrochemical response in the BT-CN composite, further enhancing its performance.…”
Section: Resultsmentioning
confidence: 99%
“…The Bi 2− x Zn x WO 6+ δ photocatalysts were dip-coated on the carbon surface (0.13 cm 2 ) of the working electrode of the commercial screen-printed electrode (DS110), following the procedure previously reported elsewhere. 42,43 Linear scanning voltammetry (LSV) at 5 mV s −1 from 0.2 to 1.4 V (V vs. Ag–AgCl) and chronoamperometry (CA) at 1.4 V ( vs. Ag–AgCl) for 1 h were conducted.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is prudent to consider these reported potentials as initial approximations for our analysis, which allows us to Environmental Science: Nano Paper discern relative trends. For example, the relatively positive VB potential of BiOI suggests the feasibility of oxidizing hydroxyl ions to generate hydroxyl radicals (1.9 V vs. NHE at pH = 7 for HO − /HO˙) 44,45 within this photocatalyst. Meanwhile, in the CB of Bi 4 O 5 I 2 , the processes, such as oxygen reduction reaction (−0.18 V vs. NHE at pH = 7 for O 2 /O 2 ˙−) 44 and/or redox reactions associated with nitazoxanide photochemistry (Fig.…”
Section: Characterization Of Materialsmentioning
confidence: 99%